2022
DOI: 10.1016/j.tranon.2021.101301
|View full text |Cite
|
Sign up to set email alerts
|

The antidiabetic drug metformin acts on the bone microenvironment to promote myeloma cell adhesion to preosteoblasts and increase myeloma tumour burden in vivo

Abstract: Highlights Metformin has unexpected indirect effects on the bone microenvironment to promote myeloma. Pretreatment with metformin indirectly increases myeloma tumour burden in vivo . Metformin increases myeloma cell adhesion to osteoblasts via osteopontin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In addition, both positive and negative associations have also been reported, as with prostate cancer, where previous year treatment with metformin was associated with an increased risk whereas exposure in the previous 2 to 7 years was associated with a decreased risk [252]. Similarly, for the use of metformin as an adjunct for the treatment of myeloma, where both beneficial anticancer and pro-cancer effects have also been reported [253,254]; these findings support the need for well-designed longterm RCTs.…”
Section: Epidemiological Studies and Clinical Trialsmentioning
confidence: 96%
“…In addition, both positive and negative associations have also been reported, as with prostate cancer, where previous year treatment with metformin was associated with an increased risk whereas exposure in the previous 2 to 7 years was associated with a decreased risk [252]. Similarly, for the use of metformin as an adjunct for the treatment of myeloma, where both beneficial anticancer and pro-cancer effects have also been reported [253,254]; these findings support the need for well-designed longterm RCTs.…”
Section: Epidemiological Studies and Clinical Trialsmentioning
confidence: 96%
“…However, an in vitro and in vivo study showed that metformin might exert an indirect pro-tumorigenic effect on MM by increasing OPN expression in preosteoblasts and thus increasing myeloma cell adherence [ 43 ]. Metformin treatment may also induce resistance to the proteasome inhibitor bortezomib in cancer cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation markers were reduced in cocultured myeloma cells with preosteoblasts treated with metformin. Mice with 5TGM1 myeloma cells pre-treated with metformin had increased tumor loads, associated with increased osteolytic bone damage and high expression of the OPN in the bone marrow [ 75 ]. In an in vitro study of nondiabetic rats with a cranial defect model, metformin promoted the differentiation of rat adipose tissue (rASCs) into bone-forming cells.…”
Section: Effects Of Metformin On Cells In Vitromentioning
confidence: 99%